Safety factors for playground equipment to promote social sustainability / Raja Mohd Aizat Akhmal Raja Mohd Rozuan, Kharizam Ismail and Wan Rabiah Wan Omar - Raja Mohd Rozuan, Raja Mohd Aizat Akhmal; Ismail, Kharizam; Wan Omar, Wan Rabiah (2019)
Playground is the place for the children to play and gain some experience, learning a new thing about the environment and makes some new friends. It should become a safe and comfortable place for them in order to smoothen their process of learning. Safe and comfortable are needs of children in order to fulfill the social sustainablity. However, the safety of the playground is questionable because there is about 3,000 cases of injuries occurred involved children at the playground. Based on these issues came out with the aim which is to suggest the safety criteria in order to enhance the level of the safety at the playground. The objective is to identify the factors related with condition of playground equipment which contribute to accidents on users at the playground. A qualitative method was used for this research by observing the condition of playground equipment. The outcome of this research is expected to assist the stakeholder Municipal Council, to enhance safety the quality of the playground in residential area in order to widen the social sustainablity towards society.